Self-Reflection Assessment in Vertebrate Zoology (SRAVZ) Using Rasch Analysis - Yuhanna, W. L.; Al Muhdhar, M. H. I.; Gofur, A.; Hassan, Z. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
Instruments that are valid, reliable, and have high consistency are needed to measure students’ self-reflection. The Self-Reflection Assessment in Vertebrate Zoology (SRAVZ) was developed to explore students’ self-reflection and abilities in the vertebrate zoology course. It is essential to test the instrument’s validity before measuring students’ abilities so that data bias does not occur. This study aims to determine the validity, whether the items are fit or misfit, and the difficulty level of SRAVZ items. SRAVZ is developed by ADDIE (Analysis, Design, Development, Implementation, Evaluation). The SRAVZ consists of 24 items tested on 135 students who have taken the vertebrate zoology course. Analysis of the Rasch model using Winstep version 4.5.2. The Rasch model shows the item reliability value at 0.97. The Cronbach alpha value at 0.94 with PTMEA Corr shows a positive value, unidimensional 48.1%. The separation index of 5.6 means that the level of grouping the items is very good. The mean square infit for SRAVZ was 0.59-1.96, and the mean square outfit value is 0.59-2.16. Data analysis shows that 24 SRAVZ items have 22 fit items and two misfit items (S3 and S5). Item numbers S3 and S5 must be excluded from the SRAVZ construction. Total items used to measure students’ self-reflection in the vertebrate zoology course were 22 items. The most difficult item is S3, and the easiest item is S6. Thus, the data indicate that the valid and reliable SRAVZ is in the good, effective, and high level of consistency category